Tin Pan Alley and the Philippines American songs of war and love, 1898-1946 : a resource guide - Walsh, Thomas P. 1940- (Lanham Scarecrow Press, 2013)
In this innovative resource, Thomas P. Walsh has compiled a unique collection of some 1,400 published and unpublished American musical compositions related to the Philippines during the American colonial era from 1898 to 1946. The book reprints a number of hard-to-find song lyrics, making them available to readers for the first time in more than a century. It also provides copyright registration numbers and dates of registration for many published and unpublished songs. Finally, more than 700 notes on particular songs and numerous links provide direct access to bibliographic records or digital copies of sheet music in libraries and collections. Exhausive in scope, Tin Pan Alley and the Philippines ia an invaluable resource for scholars and students of American history, Pacific studies, popular culture, and ethnomisicology.
Includes bibliographical references (pages 367-378) and indexes.
Electronic reproduction.
Keywords: Popular music -- United States -- 20th century -- Bibliography; Popular music -- United States -- Chronology; Philippines -- Songs and music -- Bibliography